Markedsorientert lemmaseleksjon: kriterier og prioriteringer - Eek, Øystein (Nordiske Studier i Leksikografi, 2001)
The article deals with criteria for the selection of lemmas in bilingual dictionaries from a commercial point of view. The author is an Editorial director at Kunnskapsforlaget, a Norwegian publishing company. As a publisher of dictionaries of various sizes and for various market segments, he discusses which criteria are most important for the various dictionary series. In general, they are the combined target group x use criteria,.frequency and update, and also encyclopedic representativity, culture-specific considerations and gender neutrality - their importance varying according to the type of dictionaries, whether they are dictionaries for the general market or school dictionaries for different levels. The article also includes a brief discussion of lexicographic genres within the family of dictionaries.